The Target Situation Analysis for Bahasa Inggris Syllabus at Bunda Mulia University - Murniati Murniati (Universitas Bunda Mulia, 2017)
This research focused on analyzing the process and results of pre-course needs analysis focusing in the target needs for an academic English subject (Bahasa Inggris) for students of Bunda Mulia University. The data comprised the target situation analysis conducted before the course, which was collected from interviews with the head or secretary of each department at Bunda Mulia University as the users. Another is gained from questionnaires, which were delivered to the lecturers who were teaching the subject. The other data is collected by studying relevant university documents. The target situation was analyzed during that pre-course needs analysis. The result of this research will hopefully be used as the basis in devising a syllabus for Bahasa Inggris subject at Bunda Mulia University. Keywords: Needs analysis, target situation analysis